A Review of the Synthesis of Biopolymer Hydrogel Electrolytes for Improved Electrode–Electrolyte Interfaces in Zinc-Ion Batteries - Veerle Vandeginste; Junru Wang (Energies, 2024)
The market for electric vehicles and portable and wearable electronics is expanding rapidly. Lithium-ion batteries currently dominate the market, but concerns persist regarding cost and safety. Consequently, alternative battery chemistries are investigated, with zinc-ion batteries (ZIBs) emerging as promising candidates due to their favorable characteristics, including safety, cost-effectiveness, theoretical volumetric capacity, energy density, and ease of manufacturing. Hydrogel electrolytes stand out as advantageous for ZIBs compared to aqueous electrolytes. This is attributed to their potential application in flexible batteries for wearables and their beneficial impact in suppressing water-induced side reactions, zinc dendrite formation, electrode dissolution, and the risk of water leakage. The novelty of this review lies in highlighting the advancements in the design and synthesis of biopolymer hydrogel electrolytes in ZIBs over the past six years. Notable biopolymers include cellulose, carboxymethyl cellulose, chitosan, alginate, gelatin, agar, and gum. Also, double-network and triple-network hydrogel electrolytes have been developed where biopolymers were combined with synthetic polymers, in particular, polyacrylamide. Research efforts have primarily focused on enhancing the mechanical properties and ionic conductivity of hydrogel electrolytes. Additionally, there is a concerted emphasis on improving the electrochemical performance of semi-solid-state ZIBs. Moreover, some studies have delved into self-healing and adhesive properties, anti-freezing characteristics, and the multifunctionality of hydrogels. This review paper concludes with perspectives on potential future research directions.